2006
DOI: 10.1016/j.jacc.2006.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Response During Exercise Predicts Survival in Adults With Congenital Heart Disease

Abstract: An abnormal heart rate response to exercise identifies ACHD patients with a higher risk of mortality in the midterm, even after accounting for antiarrhythmic medication and exercise capacity. Heart rate reserve is a simple and inexpensive way to identify ACHD patients at higher mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(125 citation statements)
references
References 25 publications
9
112
1
3
Order By: Relevance
“…It is reasonable to presume that patients referred for PVR in the earlier era were at a later stage of disease progression. Their reduced peak oxygen uptake 32,33 or blunted heart rate reserve 34 and increased V .…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to presume that patients referred for PVR in the earlier era were at a later stage of disease progression. Their reduced peak oxygen uptake 32,33 or blunted heart rate reserve 34 and increased V .…”
Section: Discussionmentioning
confidence: 99%
“…6 -10 Chronotropic variables remained an independent risk of mortality independent of the use of antiarrhythmic medication. 6,8,23 Furthermore, Diller et al demonstrated that chronotropic incompetence is prevalent in 62% of adults with CHD, and measures of heart rate response are as good as pV O2 in predicting mortality in this population. 6 Our current study expands on these findings by identifying a low CRI as a potential risk factor for pregnancy outcome in women with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…These new indices have not been studied widely in pediatric patients, and their relevance to this population remains uncertain. 28,29 Chronotropic incompetence (ie, an inability to increase HR to Ͼ80% of predicted at peak exercise) is common after surgery for CHD 6,28,30,31 and has been associated with a poor prognosis. 30 …”
Section: Hr During Exercisementioning
confidence: 99%